PENGARUH DARI PROBLEM POSING METHOD TERHADAP KREATIVITAS VERBAL SISWA SMP KELAS VII - Priambodo, Bagus; Listiara, Anita; Astuti, Tri Puji (Faculty of Psychology, Diponegoro University, 2013)
Verbal creativity is the ability to think fluent, flexible, and original that manifested through the words. Psychological freedom is one factor that can develop creativity. One alternative teaching methods that provide freedom in an atmosphere of learning is the Problem Posing Method (PPM) which is triggered by Paulo Freire. This research aims to determine the presence or absence of the influence of PPM on verbal creativity. Characteristic of the subjects was junior high school students in grade 7th, received conventional learning materials, and have never had learning by using PPM. This study used a non-randomized pretest-posttest control group design. Subjects in the study were divided into two, experimental group (N = 33) and control group (N= 35). The data was collected using the Verbal Creativity Test. The results of hypothesis testing used Independent Sample T Test techniques showed the differences of mean = 3.294, Î± = 0.014 with (p<0.05).Keywords: Verbal creativity, problem posing method, a test of verbal creativity, junior high school students